Cranial morphology and phylogenetic reassessment of Barreirosuchus franciscoi (Crocodylomorpha, Notosuchia), a Peirosauria from the Late Cretaceous of Brazil - Fachini, Thiago S.; Godoy, Pedro L.; Montefeltro, Felipe C. [UNESP]; Langer, Max C. (Wiley, 2025)
With nearly 30 living species of relatively similar ecological traits, Crocodylomorpha is represented today by only a small fraction of its past diversity. The well-documented crocodylomorph fossil record has revealed more than 500 taxa, with much higher ecological and morphological diversity than their extant counterparts. An example of such astonishing diversity is the Late Cretaceous rocks of the Bauru Group (southeast Brazil), from which numerous taxa are known, belonging to the clade Notosuchia. These were predominantly terrestrial taxa, some of which exhibited traits associated with omnivorous or even herbivorous feeding behaviors, such as Sphagesauridae, whereas others were adapted to a carnivore diet, such as Baurusuchidae and Peirosauridae. Among these is Barreirosuchus franciscoi, originally described as a neosuchian (Trematochampsidae) but later interpreted as a peirosaurid notosuchian. Even though included in recent morphological and phylogenetic analyses, B. franciscoi still lacked a more detailed description. Here, we provide an in-depth description of the cranial elements of B. franciscoi, using data from computed tomography and a broad sample of comparative material, including living and fossil crocodylomorphs. Also, the neuro-cavities, including the endocast, nasopharyngeal duct, and the olfactory region, were digitally reconstructed. Finally, a new phylogenetic analysis recovered B. franciscoi nested within Peirosauria, forming the Itasuchidae clade with other potentially semiaquatic species: Rukwasuchus yajabalajekundu, Pepesuchus deiseae, and Itasuchus jesuinoi. The morphological and phylogenetic reassessment of B. franciscoi indicates a semiaquatic form, highlighting the ecological diversity of notosuchians from the Bauru Group as well as the capacity of notosuchians to explore a myriad of environments.
Keywords: Bauru group; ecological diversity; Itasuchidae; Paleoneuroanatomy; Peirosauridae; phylogenetic analysis